2018
DOI: 10.1590/1807-3107bor-2018.vol32.0047
|View full text |Cite
|
Sign up to set email alerts
|

Using UV light for adhesive remnant removal after debonding of orthodontic accessories

Abstract: The objective of this study was to assess the effect of a UV lightbased auxiliary illumination on adhesive remnant (AR) removal after orthodontic debonding. Sixty human molars were divided according to the adhesive used for bonding: O-opaque; LF-low fluorescence; and HFhigh fluorescence. After debonding, the teeth were subdivided according to the AR removal method: No UV light or With UV light. After AR removal, the teeth were polished. Direct visual analysis, scanning electron microscopy (SEM) and time quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 15 publications
0
18
0
3
Order By: Relevance
“…Falsch positionierte Brackets können zu ungewollten und falschen Zahnbewegungen führen [23]. Weiterhin muss ein Überschuss ebenso wie ein Unterschuss an Befestigungsmaterial unbedingt vermieden werden, weil diese die Plaque-Akkumulation und somit das Entstehen von White-Spot-Läsionen fördern [24,25]. Eine weitere wichtige Rolle spielt die Bracket-Verlustrate, die im Sinne des Patienten und Behandlers so gering wie möglich sein sollte.…”
Section: Methodeunclassified
See 2 more Smart Citations
“…Falsch positionierte Brackets können zu ungewollten und falschen Zahnbewegungen führen [23]. Weiterhin muss ein Überschuss ebenso wie ein Unterschuss an Befestigungsmaterial unbedingt vermieden werden, weil diese die Plaque-Akkumulation und somit das Entstehen von White-Spot-Läsionen fördern [24,25]. Eine weitere wichtige Rolle spielt die Bracket-Verlustrate, die im Sinne des Patienten und Behandlers so gering wie möglich sein sollte.…”
Section: Methodeunclassified
“…Dies soll das Beseitigen von verbliebenem Material nach der Bracket-Entfernung erleichtern. Kaneshima et al [25] konnten in vitro zeigen, dass die Entfernung des fluoreszierenden Befestigungsmaterials schneller möglich war, als die des konventionellen Materials. Allerdings zeigten sich nach Entfernung des fluoreszierenden Materials mehr Beschädigungen des Zahnschmelzes.…”
Section: Materialienunclassified
See 1 more Smart Citation
“…From a clinical perspective, recent studies [10][11][12][13] have found that the use of UV light could help orthodontists view adhesives by using fluorescent agents, since they permit a more efficient removal of the remnants after debonding (Fig. 1a, b).…”
mentioning
confidence: 99%
“…1a, b). This technology also reduces the length of time needed to carry out the procedure of removal of the adhesive remnants [12]. Another important clinical aspect is that adhesive systems for orthodontic use require a minimum load for shear bond strength [14].…”
mentioning
confidence: 99%